Buckling resistance of partially encased columns embedded on walls under fire from one side - Piloto, P.A.G. (2022)
Partially encased columns (PEC) have better fire resistance when compared to bare steel columns, due to the existence of concrete between the flanges. The aim of this study is to develop a new proposal for the calculation of the buckling strength of partially encased columns, embedded on walls, under fire conditions. This proposal is based on the current calculation method proposed in Annex G of EN 1994-1-2. This study uses the finite element method to calculate the average temperature of seven components. The average temperature is then used to find the buckling resistance of composite columns when submitted to fire from one side. This solution method is carried out using 30 different cross sections. All cross sections are exposed to the standard fire curve ISO834 from one side, assuming the specific fire rating of 30, 60, 90 and 120 min.